F-18 Fluorodeoxyglucose PET/CT and Post Hoc PET/MRI in a Case of Primary Meningeal Melanomatosis - Lee, Hong Je (The Korean Society of Radiology, 2013)
Primary meningeal melanomatosis is a rare, aggressive variant of primary malignant melanoma of the central nervous system, which arises from melanocytes within the leptomeninges and carries a poor prognosis. We report a case of primary meningeal melanomatosis in a 17-year-old man, which was diagnosed with (18)F-fluorodeoxyglucose (F-18 FDG) PET/CT, and post hoc F-18 FDG PET/MRI fusion images. Whole-body F-18 FDG PET/CT was helpful in ruling out the extracranial origin of melanoma lesions, and in assessing the therapeutic response. Post hoc PET/MRI fusion images facilitated the correlation between PET and MRI images and demonstrated the hypermetabolic lesions more accurately than the unenhanced PET/CT images. Whole body F-18 FDG PET/CT and post hoc PET/MRI images might help clinicians determine the best therapeutic strategy for patients with primary meningeal melanomatosis.